The Influence of Work Environment and Competence on Work Motivation - Rosyadi Salim, Azmi (Green Publisher, 2025)
The purpose of this research is to determine and analyze: (1) Work Environment (2) Competence; (3) Work Motivation; and (4) the Influence of Work Motivation and Competence on Employee Performance at Dinas X West Java Province, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees at the Dinas X West Java Province, with a sample size of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that the Work Environment at Dinas X West Java Province is mostly rated quite well by the Employees; the competence of Employees at Dinas X West Java Province can generally be considered good, and the Work Motivation of Employees at Dinas X West Java Province is currently rated as good. Work environment and competence simultaneously affect work motivation at Dinas X West Java Province. However, partially, Work environment has a more dominant influence on work motivation than Competence. Because Work environment more dominantly influences performance, it becomes the top priority in improving work motivation. therefore, the Dinas X West Java Province is expected to improve work environment at Dinas X West Java Province by involving them in training and education, so that they can work more professionally.